Radical Versus Non-Radical Resection for Early-Stage Retroperitoneal Sarcoma: A Propensity Score-Matched Analysis - Weng, Chengxin; Wang, Jiarong; Zhao, Jichun; Yuan, Ding; Huang, Bin; Wang, Tiehao (Frontiers in Oncology, 2021)
Background: The appropriate surgical procedure for early-stage retroperitoneal sarcoma (RPS) is unclear. Thus, we used a national database to compare the outcomes of radical and non-radical resection in patients with early stage RPS. Methods: This retrospective study included 886 stage I RPS patients from 2004 to 2015 in the SEER database. Outcomes were compared using the multivariate Cox proportional hazards models and the results were presented as adjusted hazards ratio (AHR) with corresponding 95% confidence intervals (95%CIs). Propensity score-matched analyses were also performed for sensitive analyses. Results: For the 886 stage I RPS patients, 316 underwent radical resection, and 570 underwent non-radical resection, with a median follow-up of 4.58 (2.73-8.35) years. No difference was observed in overall mortality (AHR 0.84, 95%CI 0.62-1.15) or RPS-specific mortality (AHR 0.87, 95%CI 0.57-1.36) between groups. The results were similar in propensity score-matching analyses. However, subgroup analysis revealed that radical resection was associated with significantly decreased risks of overall mortality in male (AHR 0.61, 95%CI 0.38-0.98; P = .04) and in patients with radiotherapy (AHR 0.56, 95%CI 0.32-0.98; P = .04). Conclusion: Radical resection did not improve midterm survival outcomes compared with non-radical resection in overall patients with early stage RPS. However, male patients or patients who received radiotherapy might benefit from radical resection with improved overall survival.